Pengaruh Likuiditas, Leverage, Profitabilitas Dan Keputusan Investasi Terhadap Nilai Perusahaan Pada Perusahaan Sub Sektor Farmasi yang Terdaftar di Bursa Efek Indonesia - Della Dian Safitri; Sudjinan sudjinan; Nurlia nurlia (MEDIA RISET EKONOMI [MR.EKO], 2022)
The purpose of this study is to influence the variable Current Ratio, Debt to Equity Ratio, Return on Equity, and Price to Earning Ratio on Fiem Value on sub sectors of Pharmaceutical Companies Listed on the Stock Exchange. The population used in this study was 10 sub sectors Pharmaceutical Companies. And the sample is 8 sub sectors Pharmaceutical Companies. Sampling with proposive sampling method with criteria determined by researchers. The method used is multiple regression analysis method. Based on the results of the F test, Current Ratio, Debt to Equity Ratio, Return on Asset, and Price to Earnign Ratio influence jointly on Firm Value on sub sectors Pharmaceutical Companies Listed on the IDX. Based on the results of the t test, Current Ratio has a  negative and not significant effect on Firm Value. Debt to Equity Ratio has a positive and not significant effect on Firm Value. Return on Asset has a negative and not significant effect on Firm Value. Price to Earning Ratio has a negative and significant effect on Firm Value. And the result can be concluded that of the four variables Price to Earning Ratio is dominant against Firm Value on sub sectors Pharmaceutical Companies on the IDX.